Modelling And Simulation Of Bio-Oil Production From Palm Oil Biomass Via Fast Pyrolysis Using Aspen Plus - Ahmed Nassor, Akbar (Universiti Sains Malaysia, 2021)
The increase in energy consumption, limited fuel resources, massive dependency on fossil fuels, and greenhouse gas emission has resulted in increased research development on renewable energy sources. Renewable energy is the best option for meeting the current energy demands and reduce the dependence on fossil fuels. In this final year project, three palm oil biomass, namely empty fruit bunches (EFB), mesocarp fibre (MF), and palm kernel shell (PKS) were optimized to produce bio-oil via fast pyrolysis. Process modelling and simulation were carried out using ASPEN PLUS V10.0. The simulation includes pre-treatment, fast pyrolysis section, gas-solid separation, and bio-oil refining section. The model developed was successfully validated with the experimental data obtained from literature. Then, the effect of pyrolysis temperature and residence time during the fast pyrolysis of oil palm biomass were studied to maximize the yield of bio-oil product. Based on the results, the maximum bio-oil yields for EFB, MF, and PKS were 56.46 wt.%, 47.39 wt.%, and 44.03 wt.%, respectively, obtained at a temperature of 550 °C and residence time of 2 s. PKS achieved the highest biochar and gas yield of 49.77 wt.% and 37.21 wt.% at 450 °C and 600 °C, respectively due to its high lignin content. The obtained yields in this study are consistent with experimental results found in the literatures. Therefore, the model developed can be used to optimize fast pyrolysis process for different biomass sources without the need to perform complex experimental investigations. Such model will make an important contribution on the improvement and intensification of fast pyrolysis of biomass.